Incomplete Gamma and Related Functions - 8.20 Asymptotic Expansions of

From testwiki
Revision as of 16:50, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
8.20.E1 E p ( z ) = e - z z ( k = 0 n - 1 ( - 1 ) k ( p ) k z k + ( - 1 ) n ( p ) n e z z n - 1 E n + p ( z ) ) exponential-integral-En 𝑝 𝑧 superscript 𝑒 𝑧 𝑧 superscript subscript 𝑘 0 𝑛 1 superscript 1 𝑘 Pochhammer 𝑝 𝑘 superscript 𝑧 𝑘 superscript 1 𝑛 Pochhammer 𝑝 𝑛 superscript 𝑒 𝑧 superscript 𝑧 𝑛 1 exponential-integral-En 𝑛 𝑝 𝑧 {\displaystyle{\displaystyle E_{p}\left(z\right)=\frac{e^{-z}}{z}\left(\sum_{k% =0}^{n-1}(-1)^{k}\frac{{\left(p\right)_{k}}}{z^{k}}+(-1)^{n}\frac{{\left(p% \right)_{n}}e^{z}}{z^{n-1}}E_{n+p}\left(z\right)\right)}}
\genexpintE{p}@{z} = \frac{e^{-z}}{z}\left(\sum_{k=0}^{n-1}(-1)^{k}\frac{\Pochhammersym{p}{k}}{z^{k}}+(-1)^{n}\frac{\Pochhammersym{p}{n}e^{z}}{z^{n-1}}\genexpintE{n+p}@{z}\right)

Ei(p, z) = (exp(- z))/(z)*(sum((- 1)^(k)*(pochhammer(p, k))/((z)^(k)), k = 0..n - 1)+(- 1)^(n)*(pochhammer(p, n)*exp(z))/((z)^(n - 1))*Ei(n + p, z))
ExpIntegralE[p, z] == Divide[Exp[- z],z]*(Sum[(- 1)^(k)*Divide[Pochhammer[p, k],(z)^(k)], {k, 0, n - 1}, GenerateConditions->None]+(- 1)^(n)*Divide[Pochhammer[p, n]*Exp[z],(z)^(n - 1)]*ExpIntegralE[n + p, z])
Failure Successful Manual Skip!
Failed [7 / 70]
Result: Indeterminate
Test Values: {Rule[n, 3], Rule[p, -2], Rule[z, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Indeterminate
Test Values: {Rule[n, 3], Rule[p, -2], Rule[z, Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data
8.20.E4 A k + 1 ( λ ) = ( 1 - 2 k λ ) A k ( λ ) + λ ( λ + 1 ) d A k ( λ ) d λ subscript 𝐴 𝑘 1 𝜆 1 2 𝑘 𝜆 subscript 𝐴 𝑘 𝜆 𝜆 𝜆 1 derivative subscript 𝐴 𝑘 𝜆 𝜆 {\displaystyle{\displaystyle A_{k+1}(\lambda)=(1-2k\lambda)A_{k}(\lambda)+% \lambda(\lambda+1)\frac{\mathrm{d}A_{k}(\lambda)}{\mathrm{d}\lambda}}}
A_{k+1}(\lambda) = (1-2k\lambda)A_{k}(\lambda)+\lambda(\lambda+1)\deriv{A_{k}(\lambda)}{\lambda}

A[k + 1](lambda) = (1 - 2*k*lambda)*A[k](lambda)+ lambda*(lambda + 1)*diff(A[k](lambda), lambda)
Subscript[A, k + 1][\[Lambda]] == (1 - 2*k*\[Lambda])*Subscript[A, k][\[Lambda]]+ \[Lambda]*(\[Lambda]+ 1)*D[Subscript[A, k][\[Lambda]], \[Lambda]]
Failure Failure
Failed [300 / 300]
Result: -.5000000000+.133974596*I
Test Values: {lambda = 1/2*3^(1/2)+1/2*I, A[k] = 1/2*3^(1/2)+1/2*I, A[k+1] = 1/2*3^(1/2)+1/2*I, k = 1, k = 3}

Result: -.4999999993+2.133974597*I
Test Values: {lambda = 1/2*3^(1/2)+1/2*I, A[k] = 1/2*3^(1/2)+1/2*I, A[k+1] = 1/2*3^(1/2)+1/2*I, k = 2, k = 3}

... skip entries to safe data
Failed [300 / 300]
Result: Complex[-0.49999999999999944, 4.133974596215561]
Test Values: {Rule[k, 3], Rule[λ, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[Subscript[A, k], Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[Subscript[A, Plus[1, k]], Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Complex[-1.8660254037844384, 3.7679491924311224]
Test Values: {Rule[k, 3], Rule[λ, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[Subscript[A, k], Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[Subscript[A, Plus[1, k]], Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data
8.20#Ex1 A 1 ( λ ) = 1 subscript 𝐴 1 𝜆 1 {\displaystyle{\displaystyle A_{1}(\lambda)=1}}
A_{1}(\lambda) = 1

A[1](lambda) = 1
Subscript[A, 1][\[Lambda]] == 1
Skipped - no semantic math Skipped - no semantic math - -
8.20#Ex2 A 2 ( λ ) = 1 - 2 λ subscript 𝐴 2 𝜆 1 2 𝜆 {\displaystyle{\displaystyle A_{2}(\lambda)=1-2\lambda}}
A_{2}(\lambda) = 1-2\lambda

A[2](lambda) = 1 - 2*lambda
Subscript[A, 2][\[Lambda]] == 1 - 2*\[Lambda]
Skipped - no semantic math Skipped - no semantic math - -
8.20#Ex3 A 3 ( λ ) = 1 - 8 λ + 6 λ 2 subscript 𝐴 3 𝜆 1 8 𝜆 6 superscript 𝜆 2 {\displaystyle{\displaystyle A_{3}(\lambda)=1-8\lambda+6\lambda^{2}}}
A_{3}(\lambda) = 1-8\lambda+6\lambda^{2}

A[3](lambda) = 1 - 8*lambda + 6*(lambda)^(2)
Subscript[A, 3][\[Lambda]] == 1 - 8*\[Lambda]+ 6*\[Lambda]^(2)
Skipped - no semantic math Skipped - no semantic math - -